Răspuns :
ma=(a+b):2
a)[13+(-4)]:2=(13-4):2=9:2=4,5
b)[2,5+(-4)]:2=(2,5-4):2=-1,5:2=-0,75
c)[-2 1/3+(-4)]:2=(-7/3-4):2=-19/3:2=-38/3=-2,66666666666667
d)(2√2-4):2=√2-2
a)[13+(-4)]:2=(13-4):2=9:2=4,5
b)[2,5+(-4)]:2=(2,5-4):2=-1,5:2=-0,75
c)[-2 1/3+(-4)]:2=(-7/3-4):2=-19/3:2=-38/3=-2,66666666666667
d)(2√2-4):2=√2-2
a)(13+b):2=-4;13+b=-8;b=-8-13=-21
b)(2,5+b):2=-4;2,5+b=-8;b=-8-2,5=-10,5
c)(7/3+b):2=-4;7/3+b=-8;b=-8-7/3=-31/3
d)(4+b):2=-4;4+b=-8;b=-12
b)(2,5+b):2=-4;2,5+b=-8;b=-8-2,5=-10,5
c)(7/3+b):2=-4;7/3+b=-8;b=-8-7/3=-31/3
d)(4+b):2=-4;4+b=-8;b=-12